The role of functional urban areas in Mecklenburg-Vommerania - Greiving, Stefan; Winkel, Rainer (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The paper discusses different models for the organisation of functional urban areas of the six county-free cities in the federal state of Mecklenburg-Pommerania. It refers as argumentative basis to the given objectives for the re-organisation of the country structure launched by the federal government on the one hand and the known interests of the cities on the other hand. This re-organisation is regarded as indispensable in view of the ongoing demographic change, this federal state suffers from. In accordance to the development goals of the federal state itself, a remained country-free status of the six cities in combination with single incorporations of neighbouring villages and regional associations for the bigger functional urban areas of Rostock and Schwerin is preferred by this paper.
Keywords: Suburbanisation; Local government reform; Urban-regional-cooperation; Demographic change